(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This is a decidedly Tocquevillian statement in which I give voice to my concern that the spread of AI may encourage a view of the (epistemic, moral, artistic) creativity of human beings as a refined, but nonetheless mechanical, variety of imitation. In my paper, I take seriously the widespread fears about the development of increasingly sophisticated AI devices in order to understand whether they convey some morally relevant intuitions. An unbridled use of algorithms would not be a big problem as such, if it did not take place within a society in which a form of disenchantment is systematically endorsed, that actually amounts to a tacit, but, precisely for this reason, even more disturbing debunking of humanity and its ability to change for the better.